The Utilization of Nitrogen Gas as a Carrier Gas in the Determination of Hg Ions Using Cold Vapor-Atomic Absorption Spectrophotometer (CV-AAS) - Aman Sentosa Panggabean; Subur P Pasaribu; Farida Kristiana (Indonesian Journal of Chemistry, 2018)
The research about utilization of nitrogen gas as a carrier gas in the determination of Hg ions by using Cold Vapor-Atomic Absorption Spectrophotometer (CV-AAS) method has been conducted. To optimize the measurement results, several parameters that affect hydride generator have been studied. Some specified important parameters are SnCl2 concentration as reductant, acid concentration, and the analytical performance such as repeatability and reproducibility (% RSD), linearity (r), limits of detection (LOD) and limits of quantitation (LOQ), and accuracy have been studied. The results of the research showed that the nitrogen gas can be used instead of argon gas as a carrier gas. It was shown by the repeatability values as % RSD < 2/3 CV Horwitz values, the LOD was 0.0338 µg/L and the LOQ was 0.0838 µg/L. The accuracy of this method was well shown by a recovery percentage was 102.24%. Based on the result of this research, the nitrogen gas can be used as a carrier gas for the determination of Hg ions by using the CV-AAS method with valid results.